Design And Development Of Programming Learning Platform Based On Heuristic Approach In Assessment Module With Iterative And Incremental Method (case Study: Information System Telkom University) - Dewansyah Adi Saputra; Soni Fajar Surya Gumilang; Muhammad Azani Hasibuan (eProceedings of Engineering, 2015)
Abstract — In general programming learning system there should be a process of measurement. However, acommon measurement process are still many shortcomings and the high level of fraud. So the measurement is not accurate and also there are absence of a continuous learning process. The research aims to develop a platform learning based on heuristic approach focussed on assessment module especially in programming algorithm course. This module used to measure a student's ability more accurately and it will be part of a heuristic based learning process. For this platform development, it will use iterative and incremental methodology. By using the learning platform, lecturer and student can joy experience learn programming algorithm with attractive course. Index Terms— e-learning, platform learning, assessment, iterative and incremental